Relationship between Organizational Justice and Responsiveness to Patients in Selected Hospitals in North Khorasan Province, Iran - Mokhtar Ramezanpoor; Maryam Jamali; Mostafa Roshanravan (Mazandaran University of Medical Sciences, 2021)
Introduction and purpose: Justice is one of the basic aspects of providing healthcare services. Accountability is also one of the components considered by policymakers and managers of healthcare systems and paying attention to this issue in healthcare organizations is of special importance. This study aimed to investigate the relationship between organizational justice and responding to patients referring to the hospital. Methods: In this descriptive-analytical study, the samples were chosen from 387 employees of and 478 patients referring to selected hospitals in North Khorasan Province, Iran. The instrument for measuring organizational justice was the Niehoff and Morman questionnaire and the World Health Organization questionnaire was used to assess the responsiveness of hospitals' employees to patients. Results: The results showed that the rate of distributive justice among the employees was higher in public hospitals in North Khorasan Province than in the social security hospital. A significant difference was observed between the rate of responsiveness to the patients and an increase in the level of organizational justice (P≤0.05), which was increased. Conclusion: It can be concluded that by giving importance to organizational justice, it is possible to promote hope among employees to respond to patients, and consequently, solve one of the greatest challenges of the country's healthcare system, namely patient satisfaction.